IBMR-based physics e-book: Enhancing multi-representation and problem-solving ability - Wahyuni, Mustika; Jumadi, Jumadi (Universitas PGRI Kanjuruhan Malang, 2025)
Problem-solving and multi-representation abilities are essential competencies for 21st-century students, especially in physics. The use of teaching materials based on effective learning models and technology can enhance these abilities. This study aims to: develop an IBMR-based physics e-book (Investigation Based Multiple Representation) that is deemed feasible by experts, and evaluate its effectiveness in improving students’ problem-solving and multi-representation abilities. This study employs the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. A total of 48 students from a state Islamic senior high school (MAN) in Yogyakarta were randomly selected as research subjects. Data collection instruments included validation sheets, questionnaires, and tests for multi-representation and problem-solving abilities. Feasibility analysis was conducted descriptively, practicality and student response tests used ideal standard deviation, test instrument validation used Aiken’s V equation and item analysis using Item Response Theory (IRT), and effectiveness testing used MANOVA. The results showed that the IBMR-based physics e-book is feasible for use in physics learning, with validator assessments in the “Feasible” category and student responses in the “Very Good” category. Although it was not effective in improving multi-representation abilities, this e-book significantly enhanced problem-solving abilities, particularly in the evaluation aspect and the indicator of converting verbal representations to pictorial forms.